Exploring Grammatical Error in Speaking of Students University: A Case Study - Yana Karisma; Arif Bulan (Universitas Nurul Jadid, 2022)
Researchers feel it is important to conduct research on grammatical errors in students, it is based on mistakes made by students when speaking. In addition, based on previous relevant research, there are still gaps. This study aims to analyze the types of grammatical errors that occur in students of the English education study program STKIP Yapis Dompu. The research method used in this study is qualitative research with a descriptive case study approach. The results of this study indicate that there are four errors encountered in the speaking of students of the STKIP Yapis Dompu English Education Study Program, namely omission, addition, misformation, and misordering. Omission consists of five errors, addition consists of four errors. misformation consists of three errors and misordering consists of two errors. Thus, the grammatical errors found in students of the English Education Study Program STKIP Yapis Dompu are only limited to the four types mentioned above.